Microsoft office XP - O'Leary, Timothy J. (McGraw-Hill/Irwin, 2002)
Part of the highly successful Shelly Cashman Series, this text offers a clear screen-by-screen, step-by-step approach to learning the fundamentals of Microsoft Office XP.